2020
DOI: 10.1101/2020.03.19.20034447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential biochemical markers to identify severe cases among COVID-19 patients

Abstract: There is a high mortality and long hospitalization period for severe cases with 2019 novel coronavirus disease (COVID-19) pneumonia. Therefore, it makes sense to search for a potential biomarker that could rapidly and effectively identify severe cases early. Clinical samples from 28 cases of COVID-19 (8 severe cases, 20 mild cases) in Zunyi District from January 29, 2020 to February 21, 2020 were collected and otherwise statistically analysed for biochemical markers. Serum urea, creatinine (CREA) and cystatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 5 publications
1
55
0
6
Order By: Relevance
“…The model identified serum concentrations of cholinesterase, calcium, and eGFR as predictors, and elevation of the three markers associated with the risk of recurrence of PCR positivity. Previous studies found that increased levels of cholinesterase, calcium, and eGFR were associated with mild COVID-19 [32][33][34] . In our study, mild or moderate patients more likely to recur with PCR positivity post discharge.…”
Section: Discussionmentioning
confidence: 93%
“…The model identified serum concentrations of cholinesterase, calcium, and eGFR as predictors, and elevation of the three markers associated with the risk of recurrence of PCR positivity. Previous studies found that increased levels of cholinesterase, calcium, and eGFR were associated with mild COVID-19 [32][33][34] . In our study, mild or moderate patients more likely to recur with PCR positivity post discharge.…”
Section: Discussionmentioning
confidence: 93%
“…Xiang, J. et al showed that non-survivors patients presented increase in IL-6, serum urea, creatinine, cystatin C, direct bilirubin, and cholinesterase [42]. ROC curve, used to analyze the specificity and sensitivity of different variables COVID-19 patients, indicated that IL-6, PSP, He4 reflect the clinical course of the disease and might be used to predict the evolution of COVID-19 disease.…”
Section: Roc Curves Analysis Is Shown Inmentioning
confidence: 99%
“…T cells along with downregulation of IFN-c expression in severe cases was also observed [7]. In another pre-print, Xiang et al reported serum urea, creatinine and cystatin C may be potential biomarkers in severity of COVID-19 [8]. Huang et al reported higher plasma levels of interleukins (IL-2, IL-7, IL-10) and other inflammatory markers (GSCF, IP10, MCP1, MIP1A and TNF-a) in COVID-19 patients requiring ICU care versus non-ICU patients [9].…”
mentioning
confidence: 86%